Building social capital framework in organisations: exploring 'unseen' social capital in participatory decision-making. (31st July 2008) - Wong, Sam
Drawing on an ethnographic research on Mainland Chinese migrants in Hong Kong, this paper challenges the 'design principles' in building social capital. It argues that, without adequate understanding of the context and process of social interactions, these principles can destroy poor people's social networks. The concept of 'unseen' social capital offers an alternative to conceptualising social relations. This paper suggests that effective institutional interventions lie in our understanding of: history and culture of social cooperation; existing relations of reciprocity; people's livelihood priorities; individual preferred institutional environment; the interplay between new and old institutions.